Synopsis: Agricultural production and children’s diets: Evidence from rural Ethiopia - Hirvonen, Kalle; Hoddinott, John F. (International Food Policy Research Institute, 2015)
We study the relationship between pre-school children’s food consumption and household agricultural production. Using a large household survey from rural Ethiopia, we find that increasing household production diversity leads to considerable improvements in children’s diet diversity. However, we also document how this non-separability of consumption and production does not hold for households that have access to food markets. These findings imply that nutrition-sensitive agricultural interventions that push for market-integration are likely to be more effective in reducing undernutrition than those promoting production diversity.